Gordofobia em cena: estratégias discursivas contra o preconceito em vídeos do Youtube - Penas, Evelyn Cristina de Sousa (2021)
Fatphobia is the term used to describe prejudice and discrimination against fat people. It refers to the discrimination that impacts the social trajectories of these subjects with regard to accessibility, labor market, health care, affective relationships. Digital social networks occupy an important space for the circulation of narratives about the body, its idealized standards and forms of regulation. This research aimed to identify the strategies used in YouTube videos to build narratives about fatphobia and fat activism. The theoretical and methodological approach was based on the perspective of discursively oriented Critical Social Psychology. The analyzed corpus was composed of 10 videos published on the YouTube platform, selected through a search carried out between January and April 2020, based on the search for the terms “fatphobia” and “fat activism”. After the transcription and repeated visualization of the videos, a discursive analysis of the corpus was carried out in order to identify the discursive strategies present in this material. It was found that the videos reject hegemonic narratives taken for granted that the fat body necessarily represents a disease. Often using irony and satire, the videos address a fierce critique to the prejudice, embarrassment and mockery against fat people that freely circulate in a fatphobic culture. Although humour has played an important role in the stigmatization of fat people, it has also been used as a tool to challenge the dominant discourses that model, normalize and regulate their bodies. In this sense humour shows up as powerful strategy of education and critique that propose a more inclusive society for different modes of existence.